External Validation of UDCA Response Score in Slovak and Croatian Patients with Primary Biliary Cholangitis. (23rd June 2021) - Gazda, Jakub; Janicko, Martin; Drazilova, Sylvia; Grgurevic, Ivica; Kanizaj, Tajana Filipec; Koller, Tomas; Bodorovska, Beatrica; Mijic, Maja; Mikolasevic, Ivana; Stromar, Ivana Knezevic; Kucinsky, Branislav; Gazda, Matej; et al.
Abstract : Background . Ursodeoxycholic acid response score (URS) is a prognostic model that estimates the baseline probability of treatment response after 12 months of ursodeoxycholic acid (UDCA) therapy in patients with primary biliary cholangitis (PBC). Aim . To independently evaluate the predictive performance of the URS model. Methods . We used a cohort of Slovak and Croatian treatment-naïve PBC patients to quantify the discrimination ability using the area under receiver operating characteristic curve (AUROC) and its 95% confidence interval (CI). Furthermore, we evaluated the calibration using calibration belts. The primary outcome was treatment response after 12 months of UDCA therapy defined as values of alkaline phosphatase ≤1.67 × upper limit of normal. Results . One hundred and ninety-four patients were included. Median pretreatment age was 56 years (interquartile range 49–62). Treatment response was achieved in 79.38% of patients. AUROC of the URS was 0.81 (95% CI 0.73–0.88) and the calibration belt revealed that response rates were correctly estimated by predicted probabilities. Conclusion . Our results confirm that the URS can be used in treatment-naïve PBC patients for estimating the treatment response probability after 12 months of UDCA therapy.